Development of a User-Informed Social Resource Guide to Improve Identification and Management of Psychosocial Concerns: A Model for the Free Clinic Setting - Nicholas Peoples; Mary Fang; Panayiotis Kontoyiannis; Colton Andrews; Dana Clark (Journal of Student-Run Clinics, 2023)
Background: Resource guides, which consolidate information on community resources, are an important tool for linking vulnerable patients to social and health services. Many existing guides, however, are 1) out-of-date, 2) lack user-friendly design features, and 3) lack instructions for how to access services. We describe an effort to optimize a social resource guide for people experiencing homelessness, where the process may serve as a model for other free clinic settings.Methods: From April 2021 to April 2022, we launched a phased social liaison volunteer program at HOMES Clinic, driving the development of a unique community-informed social resource guide. Specifically, we 1) collected and verified word-of-mouth data from the userbase of various social services (i.e. “street smarts”), and 2) designed a user-friendly interface with easy-to-use deliverables for patients.Results: The HOMES Social Resource Guide facilitates care coordination in both the clinic and street settings. A key design feature is that information for each resource is condensed into a 3.5x2.0” card that fits easily into pockets or wallets. The front contains logistic information (e.g., hours, location, phone) and the back describes how to qualify for and access each service. Cards are organized into a binder and provided to patients by trained volunteers in a need-based manner. Since qualifying for many services is contingent upon first meeting other milestones, the guide includes algorithms to ensure we provide all necessary information to meet any identified need. Information is re-verified/updated every six months. The platform is cost-effective: the raw materials together cost $20.Discussion: While resource guides are not a new invention, we propose that our increased emphasis on simplicity, user-friendliness, community participation, and meeting end-user needs offer clear advantages over other common design paradigms. These principles may be relevant to other free clinics in meeting the diverse needs of underserved populations.